A new approach for drug discovery from glycobiology and phage-displayed peptide library technology - Taki, Takao; Ishikawa, Dai; Ogino, Koichi; Tanaka, Michinori; Oku, Naoto; Asai, Tomohiro; Popa, Iuliana; Portoukalian, Jacques (Biochimica et biophysica acta, 2008)
Peptides which mimic functional activities of glycosphingolipids were prepared by a technology of phage-displayed peptide library using monoclonal antibodies against glycosphingolipids. These peptides were named glyco-replica peptides. Peptides prepared with anti-GD1α antibody by this technology were found to contain WHW as common motif, and they showed suppressive activity not only on adhesion between hepatic sinusoidal endothelial cells and lymphosarcoma RAW117-H10 cells, but also on metastasis of the tumor cell to the liver and lung. The WHW motif seems to be important to mimic the functional activity of the ganglioside GD1α. Next, we prepared GD3-replica peptides using a monoclonal antibody against GD3 (4F6). A peptide, GD3-P4 with highest affinity to 4F6 was used to immunize mice to examine if the mice show their immune response to raise antibodies against GD3. We confirmed the immune response and succeeded in the production of a monoclonal antibody (3D2) against GD3. The monoclonal antibody 3D2 showed specific binding to GD3 on a thin-layer chromatography plate and also melanoma tissues. Interestingly, the amino acid sequence of the CDR regions of light and heavy chains showed high similarity with those of the original GD3 monoclonal antibody (4F6) used for the preparation of GD3-replica peptide. The technology of the phage-displayed peptide library was applied to in vivo bio-panning study using an angiogenesis experimental model. The obtained peptides were found to show strong binding property to the neo-vasculature system and to be quite useful to carry an anti-tumor drug to the tumor tissue. Based on these experimental results, we discuss about some applications of this method to drug discovery.